Study on the effectiveness of sulfate-reducing bacteria to remove Pb(II) and Zn(II) in tailings and acid mine drainage - Dong, Yanrong; Gao, Ziqing; Di, Junzhen; Wang, Dong; Yang, Zhenhua; Guo, Xuying; Zhu, Xiaotong (Frontiers in Microbiology, 2024)
In view of the water and soil pollution of Pb(Ⅱ), Zn(Ⅱ) and other heavy metals in tailings and acid mine drainage (AMD), we explored the removal effect of sulfate reducing bacteria (SRB) on Pb(Ⅱ), Zn(Ⅱ) and other pollutants in solution and tailings based on the microbial treatment technology. At the same time, combining with scanning electron microscope-Energy Dispersive Spectroscopy (SEM-EDS), X-ray diffraction (XRD) and X-ray fluorescence (XRF), the mechanism of SRB treatment of tailings was revealed. The results showed that SRB had a strong removal capacity for Zn(Ⅱ) at 0-40 mg/L, and Zn(Ⅱ) at 60-100 mg/L would inhibit the growth of SRB. SRB had a very strong ability to remove Pb(II) from the solution. When the initial Pb(II) concentration was 10-50 mg/L, the removal percentage of Pb(II) reached 100%. SRB treatment can effectively immobilize the pollutants leached from the tailings. With the increase of the amount of tailings added to each layer, the ability of SRB to treat the pollutants in the tailings shows a downward trend. When 1 cm of tailing sands was added to each layer, SRB had the best effect on tailing sands treatment. After treatment, the immobilization rates of SO42-, Fe(Ⅲ), Mn(Ⅱ), Pb(Ⅱ), Zn(Ⅱ), Cu(Ⅱ) and total chromium in the leachate of 1# tailing sands were 95.44%, 100%, 90.88%, 100%, 96.20%, 86.23% and 93.34% respectively. After the treatment of tailings by SRB, although the tailings can be solidified into a cohesive mass from loose granular particles, the mechanical strength is less than 0.2 MPa. The predominant roles in treating tailings by mixing SRB are played by Desulfovibrio and Desulfohalotomaculum. The S2- and carbonate produced by mixed SRB during the treatment of tailings can metabolize sulfate and combine with the heavy metal ions released by the tailings to form FeS, MnS, ZnS, CuS, PbS, Cr2S3, CaCO3, MnCO3 and other precipitated particles, which were attached to the surface of the tailings, reducing the environmental pollution of the tailings to the water and soil around the mining area.